Examining the Role of Leisure in Navigating Spousal Death: A Phenomenological Multi-Case Study of Widowhood - Thomas P. Sweeney; Jennifer Zorotovich (Journal of Ageing and Longevity, 2023)
The current study will explore the post-pandemic bereavement window of widowed caregivers who experienced higher degrees of social isolation and the ways in which leisure was used to cope. A phenomenological multi-case study technique was used to explore the “multiple realities” among female caregivers whose social convoys suffered pre-pandemic because of spousal caregiving and were further impacted by COVID-19 mitigation strategies during the pandemic. Initial analyses utilized the two-cycle approach, as defined by Saldana. In the initial cycle, the researchers independently immersed themselves in the raw data gathered during participant interviews and engaged in open coding to discern concepts, patterns, themes, and categories associated with the multiple realities among the widows whose leisure participation was affected due to the strain of spousal caregiving and exacerbated by COVID-19 mitigation strategies. After completing the first cycle, the researchers then moved to the second phase, thematic analysis, which sought to develop a more structured framework by which to understand the data by identifying, analyzing, and reporting patterns (e.g., themes) within it. A qualitative comparison technique was then employed to deepen our understanding of individuals’ lived experiences. Thematic findings revealed three areas of similarities: Social isolation from caregiving, using leisure to self-focus and explore future possibilities, and core groups.